Thinking about ordinary things : a short invitation to philosophy - Sokol, Jan, 1936-2021; Pauzerová, Markéta; Cairn, Paul; ebrary, Inc. (Prague : Charles University in Prague, Karolinum Press, 2013)
How to teach philosophy to young dissidents, excluded from higher education by the communist regime? The author of this book, Czech philosopher, former dissident, software developer and occasional politician, tries to carry over this experience into his university lectures. It is not a talk about philosophy or philosophers, but rather an invitation: its aim is first to excite the reader´s interest and to lead him or her to think philosophically by himself. In some 30 short chapters, covering a broad spectrum of topics and followed by questions, the reader is shown that philosophy is not only a special discipline, but rather a habit of thought, which can and should be applied anywhere.
1, Philosophy: between science, art and myth -- 2, How we see and hear -- 3, Perception and attention -- 4, Things, words and names -- 5, Language and thought -- 6, Man in the world --7, Holiday and everyday, myth and Logos -- 8, You and I -- 9, Action and freedom -- 10, Play -- 11, Language as play -- 12, Time -- 13, Science and knowledge -- 14, Thruth -- 15, Scale and ratio -- 16, Likeness and imitation -- 17, Life -- 18, Nature -- 19, Necessity and chance -- 20, Technique and technology -- 21, Society, institutions and state -- 22, Values and money -- 23, Custom and society -- 24, Morality and ethics -- 25, Law -- 26, Text and interpretation -- 27, The City -- 28, History -- 29, What happens in history? -- 30, Civilisation, culture, and religion -- 31, Tolerance and pluralism -- 32, Man and the world
Elektronická reprodukce.
Keywords: filozofie; filozofické myšlení; philosophy; philosophical thought; přednášky; e-knihy online; lectures; e-books online